Managing diversity in higher education: Understanding and tackling ethnic stratification in social comfort - April, K.; Loubser, J.; Ozbilgin, M.; Ariss, A. Al (South African Journal of Higher Education, 2016)
Drawing on a higher education comparative study of 184 African-American students in the USA and 310 black South African undergraduate students in SA, we identify patterns of social comfort in relation to ethnic difference and similarity. Respective groups were administered identical Revised Social Scales. Factor analysis suggested two major categories of social comfort for African-American students, while black South African students yielded three major emergent groups. A high correlation between these non-intimate and intimate categories were found among the out-group attitudes of African-American students, indicative of similarity in sample group attitude. The converse was found with black students; low variable correlation indicates high variability in question-answering and low similarity in approach to various social situations with out-group.